Regulation Of Cryptocurrency In Indonesia: An Integrative Approach Between Positive Law And Islamic Law For Risk Mitigation - Ahmad Azim Aufaq; Bakhrul Huda (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Cryptocurrency in Indonesia faces complex regulatory challenges, given its legal status as a digital asset but its illegality as a means of payment. This legal uncertainty is exacerbated by the incompatibility of cryptocurrency practices with Sharia principles, particularly due to elements of gharar (uncertainty) and maysir (gambling), which are prohibited in Islamic law. This study aims to examine cryptocurrency regulation through an approach that integrates positive law and Islamic law, while formulating a risk mitigation model to ensure compliance with both legal systems. Employing normative legal methods and a juridical-philosophical approach, this research identifies the existing legal dualism and proposes the